2016
DOI: 10.1111/jzo.12433
|View full text |Cite
|
Sign up to set email alerts
|

From embryos to larvae: seven‐month‐long paternal care by male Japanese giant salamander

Abstract: Parental care is remarkably diverse in its modes both within and across taxa. Within amphibians, various pre‐ and post‐hatching care behaviours have been described in frogs. In contrast, the current knowledge about salamander parental care is largely limited to pre‐hatching attendance by females. In particular, post‐hatching parental care by male salamanders have never been described and analysed in detail. A recent study revealed various modes of pre‐hatching care provided by male Japanese giant salamanders (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Although historical anecdotes described egg fanning and defense, recent field observations and video monitoring have revealed an extended period of pre-and posthatching parental care in the Japanese giant salamander, Andrias japonicus (Okada et al 2015;Takahashi et al 2017). Large males (''den-masters'') occupy nesting burrows along stream banks, performing tail fanning, agitation, filial hygienic cannibalism, and active predator defense (Okada et al 2015), both before hatching (1-2 mo) and with juveniles (up to 5 mo; Takahashi et al 2017). Unfortunately, small sample sizes (n ¼ 2) impede inferences about the causes, correlates, and function(s) of these behaviors.…”
Section: Urodelesmentioning
confidence: 99%
“…Although historical anecdotes described egg fanning and defense, recent field observations and video monitoring have revealed an extended period of pre-and posthatching parental care in the Japanese giant salamander, Andrias japonicus (Okada et al 2015;Takahashi et al 2017). Large males (''den-masters'') occupy nesting burrows along stream banks, performing tail fanning, agitation, filial hygienic cannibalism, and active predator defense (Okada et al 2015), both before hatching (1-2 mo) and with juveniles (up to 5 mo; Takahashi et al 2017). Unfortunately, small sample sizes (n ¼ 2) impede inferences about the causes, correlates, and function(s) of these behaviors.…”
Section: Urodelesmentioning
confidence: 99%
“…() and Takahashi et al . () found that male A. japonicus den masters exhibit hygienic filial cannibalism for their embryos and newly hatched larvae; den masters consume eggs and larvae showing signs of maldevelopment, death or water mould infection, which would likely prevent water mould infection from spreading to healthy offspring. Nest cleaning in the form of vigorously stirring the sand throughout the preoviposition period likely reduces the amount of organic matter in the den, such as leaves, twigs, carcasses of small aquatic creatures and waste, which provide food sources for water moulds (Padgett & Heitman, ; Czeczuga, Kozłowska & Godlewska, ; Czeczuga, Godlewska & Kozlowska, ; Czeczuga & Mazalska, ).…”
Section: Discussionmentioning
confidence: 99%
“…() and Takahashi et al . () recently detailed prolonged and complex postoviposition parental care by male A. japonicus . The present study extended the current knowledge by revealing behavioural convergence in parental care between the fish and the fully aquatic giant salamanders not only in postoviposition but also in preoviposition care by males in the form of nest cleaning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations